An Insertion Mutation in Bra032169 Encoding a Histone Methyltransferase Is Responsible for Early Bolting in Chinese Cabbage (Brassica rapa L. ssp. pekinensis) - Huang, Shengnan; Hou, Li; Fu, Wei; Liu, Zhiyong; Li, Chengyu; Li, Xiang; Feng, Hui (Frontiers in Plant Science, 2020)
Bolting is an important agronomic character of the Chinese cabbage, but premature bolting can greatly reduce its commercial value, yield, and quality. Here, early-bolting mutant 1 (ebm1) was obtained from a Chinese cabbage doubled haploid (DH) line ‘FT’, by using an isolated microspore culture and ethyl methanesulfonate (EMS) mutagenesis. The ebm1 was found to bolt extremely earlier than the wild type ‘FT’. Genetic analysis indicated that the phenotype of the ebm1 was controlled by a single recessive nuclear gene. Using a mapping population of 1502 recessive homozygous F2 individuals with the ebm1 phenotype, the ebm1 gene was mapped to between the markers SSRhl-53 and SSRhl-61 on chromosome A04 by using SSR markers, and its physical distance was 73.4 kb. Seven genes were predicted in the target region and then cloned and sequenced; the only difference in the sequences of the ebm1 and ‘FT’ genes was with Bra032169. Unlike that in ‘FT’, the Bra032169 in ebm1 had a novel 53 bp insertion that caused the termination of amino acid coding. The mutation was not consistent with EMS mutagenesis, and thus, may have been caused by spontaneous mutations during the microspore culture. Based on the gene annotation information, Bra032169 was found to encode the histone methyltransferase CURLY LEAF (CLF) in Arabidopsis thaliana. CLF regulates the expression of flowering-related genes. Further genotyping revealed that the early-bolting phenotype was fully co-segregated with the insertion mutation, suggesting that Bra032169 was the most likely candidate gene for ebm1. No significant differences were noted in the Bra032169 expression levels between the ebm1 and ‘FT’. However, the expression levels of the flowering-related genes FLC, FT, AG, and SEP3 were significantly higher in the ebm1 than in the ‘FT’. Thus, the mutation of Bra032169 is responsible for the early-bolting trait in Chinese cabbage. These results provide foundation information to help understand the molecular mechanisms of bolting in the Chinese cabbage.